Pelatihan Sapta Pesona sebagai Upaya Peningkatan Pelayanan Prima pada Pelaku Pariwisata di Desa Bedono Kabupaten Demak - Aulia Restu Ariyanto Putri; Narolita, Mella; Hamsar Suci Amalia (Yayasan Literasi Altruis Khatulistiwa, 2026)
Bedono Tourism Village is known as “Kampung Teles” due to the phenomenon of abrasion and daily tidal flooding. It has unique tourism potential but faces obstacles in terms of service quality. Without immediate intervention, the degradation of service quality amidst these extreme environmental conditions is feared to stifle tourist interest and paralyze the burgeoning local economy. This study aims to improve the capacity of human resources, namely tourism practitioners in Bedono Tourism Village, through Sapta Pesona training as the basis for excellent service. The method used is a participatory approach involving 11 members of the Tourism Awareness Group (Pokdarwis) through the stages of needs analysis, material presentation, case discussions, and simulations (role-play). Evaluation was conducted using a pretest-posttest design to measure the increase in participants’ knowledge. The results showed that before the training, service was still spontaneous and not yet standardized. After the training, there was a 26.8% increase in participants' knowledge, with the average score increasing from 54.5% to 81.3%. Participants were able to integrate the dimensions of excellent service (reliability, responsiveness, assurance, empathy, and physical evidence) into the seven elements of Sapta Pesona. In conclusion, this training succeeded in strengthening the initial capital of human resources in building professional and sustainable services. The recommendations in this study are the preparation of written Service Operational Standards from Pokdarwis, infrastructure improvements from the local government, and the strengthening of a hospitable culture from the local community to increase tourist satisfaction amid environmental limitations.